2017
DOI: 10.5194/acp-17-8789-2017
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric chemistry, sources and sinks of carbon suboxide, C<sub>3</sub>O<sub>2</sub>

Abstract: Abstract. Carbon suboxide, O = C = C = C = O, has been detected in ambient air samples and has the potential to be a noxious pollutant and oxidant precursor; however, its lifetime and fate in the atmosphere are largely unknown. In this work, we collect an extensive set of studies on the atmospheric chemistry of C 3 O 2 . Rate coefficients for the reactions of C 3 O 2 with OH radicals and ozone were determined as k OH = (2.6 ± 0.5) × 10 −12 cm 3 molecule −1 s −1 at 295 K (independent of pressure between ∼ 25 an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…10 Early iterations of PTR-MS were equipped with a quadrupole detector allowing only 1 amu mass resolution, so that any species generating signals between 69 and 70 amu were potential interferents with the accurate quantification of isoprene. Prior outside air studies noted the potential of cyclopentene, furan, 2-methyl-3-buten-ol 11 and even the minor constituent carbon suboxide (C 3 O 2 12 ) to contribute to m / z 69. More recent versions of the PTR-MS have been equipped with a time of flight mass spectrometer capable of higher mass resolution allowing identification of the exact molecular formula; they are therefore less prone to interference through fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…10 Early iterations of PTR-MS were equipped with a quadrupole detector allowing only 1 amu mass resolution, so that any species generating signals between 69 and 70 amu were potential interferents with the accurate quantification of isoprene. Prior outside air studies noted the potential of cyclopentene, furan, 2-methyl-3-buten-ol 11 and even the minor constituent carbon suboxide (C 3 O 2 12 ) to contribute to m / z 69. More recent versions of the PTR-MS have been equipped with a time of flight mass spectrometer capable of higher mass resolution allowing identification of the exact molecular formula; they are therefore less prone to interference through fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…A study in a ponderosa pine forest demonstrated that NO + chemistry allows selective measurements of isoprene and MBO 187. In addition to C 5 H 8 H + and C 4 H 4 OH + , a small peak (C 3 O 2 H + , m/z 68.997) attributed to carbon suboxide is observed at m/z 69 in PTR-TOF mass spectra 188. m/z 71.…”
mentioning
confidence: 99%
“…28 Meanwhile, regarding another substance generated during radiolysis, C 3 O 2 , a report has studied its atmospheric chemical properties. 29 The research involved investigating its spectral characteristics at infrared and ultraviolet wavelengths to assess its greenhouse effect and to determine its atmospheric photolysis rate constants. and two CO, making the photolysis of C 3 O 2 a direct source of C atoms, 31 which can in turn participate in other reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while the existence of CO 4 is challenging to capture under current experimental conditions in the reaction of CO + O 3 to generate CO 4 , the theoretical investigation of the lowest singlet potential energy surface of this molecule has been explored . Meanwhile, regarding another substance generated during radiolysis, C 3 O 2 , a report has studied its atmospheric chemical properties . The research involved investigating its spectral characteristics at infrared and ultraviolet wavelengths to assess its greenhouse effect and to determine its atmospheric photolysis rate constants.…”
Section: Introductionmentioning
confidence: 99%